Survey the effect of nitroglycerin ointment on primary dysmenorrhea among the students resident of selecteddormitory of Tehran university of medical sciences in 1999 - M. Modarres; Sh Ghasizadeh; A . Mehran; T . Dadghah (Tehran University of Medical Sciences, 2001)
This study was a randomized double - blind controlled clinical trial to investigate the effect of nitroglycerine ointment on primary dysmenorrhea and its side effects among the students resident of selected dormitory of Tehran university of medical sciences in 1999."nThe investigated units consisted of 112 students suffering from primary dysmenorrhea grade 2 and 3."nThe samples were randomly assigned into two equal groups : control Group (56 students )and experimental group (56 students )as well."nThe severity of pain and side effects were evaluated once before and five times after applying the ointment. Then ,a comparison was made to assess the effect of drug and placebo on two groups according to severity of pain and side effects."nThe results showed that severity of pain in case group was significantly lower than control group during 30 minutes and one, two and four hours after applying the ointment, (in all cases p=o.oo)Moreover , 15 -30 minutes after applying the ointment, it was effective in relieving pain and it reached its highest degree when two hours passed, then the effectiveness of the ointment in relieving pain was reduced , but it continued to be effective within four hours after applying as well. Furthermore, the findings revealed that 5 mg of Nitroglycerine 1% was effective in relieving primary dysmenorrhea, however, it was accompanied with following side effects in two groups: headache 21.4% in case group VS 1.8% in control group (p=0.00), dizziness 21.4%in case group VS 1.8% in control group (p=0.00), hotflashing 35.7% in case group vs 1.8% in control group (p=0.00), arrhythmia 10.8% in case group VS 0% in control group (p= C.05), a significant falling in systolic and diastolic blood pressure (p=0.05) and a significant increasing in heart beat. (p=0.05).